Dual inhibition of BET and HAT/p300 suppresses colorectal cancer via DR5- and p53/PUMA-mediated cell death - Kuang, Chaoyuan; Tong, Jingshan; Ermine, Kaylee; Cai, Manbo; Dai, Fujun; Hao, Suisui; Giles, Francis; Huang, Yi; Yu, Jian; Zhang, Lin (Frontiers in Oncology, 2022)
Background Colorectal cancer (CRC) frequently has a dysregulated epigenome causing aberrant up-regulation of oncogenes such as c-MYC. Bromodomain and extra-terminal domain (BET) proteins and histone acetyltransferases (HAT) are epigenetic regulatory proteins that create and maintain epigenetic states supporting oncogenesis. BET inhibitors and HAT inhibitors are currently being investigated as cancer therapeutics due to their ability to suppress cancer-promoting epigenetic modifiers. Due to the extensive molecular crosstalk between BET proteins and HAT proteins, we hypothesized that dual inhibition of BET and HAT could more potently inhibit CRC cells than inhibition of each individual protein. Methods We investigated the activity and mechanisms of a dual BET and HAT inhibitor, NEO2734, in CRC cell lines and mouse xenografts. MTS, flow cytometry, and microscopy were used to assess cell viability. qPCR, Western blotting, and immunofluorescent staining were used to assess mechanisms of action. Results We found that NEO2734 more potently suppresses CRC cell growth than first generation BET inhibitors, regardless of the status of common CRC driver mutations. We previously showed that BET inhibitors upregulate DR5 to induce extrinsic apoptosis. In the current study, we show that NEO2734 treatment induces CRC cell apoptosis via both the intrinsic and extrinsic apoptosis pathways. NEO2734 increases p53 expression and subsequently increased expression of the p53-upregulated mediator of apoptosis (PUMA), which is a critical mechanism for activating intrinsic apoptosis. We demonstrate that inhibition of either the intrinsic or extrinsic branches of apoptosis partially rescues CRC cells from NEO2734 treatment, while the dual inhibition of both branches of apoptosis more strongly rescues CRC cells from NEO2734 treatment. Finally, we show that NEO2734 monotherapy is able to suppress tumor growth in CRC xenografts by inducing apoptosis. Conclusions Our study demonstrates NEO2734 potently suppresses CRC cells in vitro and in vivo by simultaneously upregulating PUMA and DR5 to induce cell death. Further studies of NEO2734 for treating CRC are warranted.